PERBANDINGAN METODE KERJA ANTARA MESIN CONCRETE PAVER DAN MESIN WACKER PADA MAINROAD LAJUR KIRI SEKSI 1A PROYEK JALAN TOL SURABAYA - MOJOKERTO - , MUSTOFA AGUNG S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Freeway is public road thas is part of system as a network of roads and national road users are required to pay. Operation of freeway is intended to achieve equitable development and the outcome as well as the balance in regional development with due regard, so that can be achieved by building freeway which was funded by road user. The purpose of the freeway to increase the efficiency of distribution services to support economic growth, especially in area that have a high level of development. The method used in this work is rigid pavement using 2 machines, slipform concrete paver 500 and vibratory truss screed neuson. Selection of used machinary aims to maximize human resources, and reduse budget cost. In rigid pavement using slipform concrete paver machine 500 is much more efficient and the results of rigid pavement is better than use the machine wacker vibratory truss screed NEUSON. wacker engine can be used on areas that are narrow and irregular in contrast to the paver machine can not do in the area.